Inocybe aureocitrina (Inocybaceae), a new species of section Rimosae from Mediterranean evergreen oak forests - ESTEVE-RAVENTóS, F (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
The new agaricoid species Inocybe aureocitrina, belonging to section Rimosae, is described and illustrated based on morphological and ecological characters. It is recognized by the pale citrine yellow when young to golden yellow or orange yellow pileus colour at maturity, habitat in evergreen oak calcareous forests and especially by the rather small spores, broadly ellipsoid and not reniform in profile. A comparison with the holotypes of two close taxa with yellowish colours, e.g. Inocybe obsoleta var. lutea and Inocybe fastigiata var. cerina, is presented. Illustrations of the macro- and micro-morphological features of this new species are given.
doi: 10.1080/11263504.2013.877532
Keywords: Evergreen oak forests; Inocybe fastigiata var. cerina; Inocybe obsoleta var. lutea; Mediterranean ecosystems; morphology; Spanish mycobiota; taxonomy